1996
DOI: 10.3109/00048679609065020
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Laughing and Crying

Abstract: Clinicians should remain vigilant for these symptoms, and offer effective treatments, such as antidepressants, where indicated. Further research is needed to delineate the underlying neurobiological correlates of pathological laughing and crying. The efficacy of both pharmacological and non-pharmacological interventions requires critical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 41 publications
1
74
0
6
Order By: Relevance
“…1,3,8,33 We conducted an online survey among patients in the USA with six underlying conditions commonly associated with PBA -ALS, MS, stroke, AD/dementia, TBI, and PD -in order to prospectively estimate the overall prevalence of PBA and quantify the extent to which PBA is diagnosed and treated. Secondary goals were to investigate patterns of physician recognition, diagnosis, and treatment of PBA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,8,33 We conducted an online survey among patients in the USA with six underlying conditions commonly associated with PBA -ALS, MS, stroke, AD/dementia, TBI, and PD -in order to prospectively estimate the overall prevalence of PBA and quantify the extent to which PBA is diagnosed and treated. Secondary goals were to investigate patterns of physician recognition, diagnosis, and treatment of PBA.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Clinical case and study data have shown that PBA may cause severe distress, embarrassment, and social disability among patients. 3,[7][8][9][10] In addition, studies have shown that patients with PBA or similar syndromes experience an increased incidence of depression, 11 impairments in executive function 12 and sexual function, 13 and ability to perform activities of daily living 14 10,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] ). This variability is probably due to differences in the populations studied and in the criteria and methods used for identifying PBA.…”
Section: Introductionmentioning
confidence: 99%
“…Tateno et al (2004) mostraram que aqueles que apresentavam IEED eram significativamente mais depressivos, ansiosos e agressivos quando comparados com pacientes sem o transtorno. Na esclerose lateral amiotrófica (ELA), a presença de sintomas que sugiram acometimento bulbar, como distúrbios da fala e da deglutição, constitui um preditor para o aparecimento de choro e riso patológicos (Schiffer et al, 2006;Dark et al, 1996). Uma prevalência de 49% de IEED foi reportada por Gallagher (1989) em um estudo realizado com 73 pacientes portadores de ELA, dos quais 27% apresentavam ambos, choro e riso patológicos; 12%, apenas choro patológico e 9,5%, apenas riso patológico.…”
Section: Epidemiologiaunclassified
“…[13] This syndrome occurs secondary to neurological disease or brain injury, including Alzheimer’s disease or dementia, multiple sclerosis, Parkinson’s disease, amyotrophic lateral sclerosis, stroke and traumatic brain injury, among other conditions. [2] PBA episodes often cause severe embarrassment and social dysfunction, and can lead to social isolation, reduced quality of life and impaired function for patients, independent of the burdens of the underlying, primary disorder.…”
Section: Introductionmentioning
confidence: 99%